From Policemen to Revolutionaries. - Cao, Yin (Studies in Global Migration History Ser., 2017)
From Policemen to Revolutionaries uncovers the less-known story of Sikh emigrants in Shanghai in the late nineteenth and early twentieth centuries. Yin Cao argues that the cross-border circulation of personnel and knowledge across the British colonial and the Sikh diasporic networks, facilitated the formation of the Sikh community in Shanghai, eventually making this Chinese city one of the overseas hubs of the Indian nationalist struggle. By adopting a translocal approach, this study elaborates on how the flow of Sikh emigrants, largely regarded as subalterns, initially strengthened but eventually unhinged British colonial rule in East and Southeast Asia.